Influence of leptin and its receptors on individuals under chronic social stress behavior - Mélo, Renata M. F.; Barbosa, Rafaela S.; Ozório, Victória L.; Oliveira, Gabriel M.; Horita, Samuel I. M.; Henriques-Pons, Andrea; Araújo-Jorge, Tânia C.; Fragoso, Viviane M. S. (Frontiers in Endocrinology, 2024)
Stress is the body's physiological reaction to a dangerous or threatening situation, leading to a state of alertness. This reaction is necessary for developing an effective adaptive response to stress and maintaining the body's homeostasis. Chronic stress, caused mainly by social stress, is what primarily affects the world's population. In the last decades, the emergence of psychological disorders in humans has become more frequent, and one of the symptoms that can be observed is aggressiveness. In the brain, stress can cause neuronal circuit alterations related to the action of hormones in the central nervous system. Leptin, for example, is a hormone capable of acting in brain regions and neuronal circuits important for behavioral and emotional regulation. This study investigated the correlation between chronic social stress, neuroendocrine disorders, and individual behavioral changes. Then, leptin and its receptors' anatomical distribution were evaluated in the brains of mice subjected to a protocol of chronic social stress. The model of spontaneous aggression (MSA) is based on grouping young mice and posterior regrouping of the same animals as adults. According to the regrouping social stress, we categorized the mice into i) harmonic, ii) attacked, and iii) aggressive animals. For leptin hormone evaluation, we quantified plasma and brain concentrations by ELISA and evaluated its receptor and isoform expression by western blotting. Moreover, we verified whether stress or changes in leptin levels interfered with the animal's body weight. Only attacked animals showed reduced plasma leptin concentration and weight gain, besides a higher expression of the high-molecular-weight leptin receptor in the amygdala and the low-molecular-weight receptor in the hippocampal region. Aggressive animals showed a reduction in the cerebral concentration of leptin in the hippocampus and a reduced highand low-molecular-weight leptin receptor expression in the amygdala. The harmonic animals showed a reduction in the cerebral concentration of leptin in the pituitary and a reduced expression of the high-molecular-weight leptin receptor in the amygdala. We then suggest that leptin and its receptors' expression in plasma and specific brain areas are involved in how individuals react in stressful situations, such as regrouping stress in MSA.